Clinical evaluation of computer-aided design and three-dimensional printing for completely edentulous mandibular custom tray fabrication: assessing clinician satisfaction - Zhao, Tian; Weng, Yi; Li, Ning; Gao, Yiming (Frontiers in Bioengineering and Biotechnology, 2025)
This study evaluates prosthodontists’ satisfaction and efficiency of custom tray fabrication methods in completely edentulous mandibular jaw patients. A digital workflow was established, incorporating 3D scanning for preliminary impressions, CAD for designing border extensions and ensuring uniform 3D space, and 3D printing for tray fabrication. Three methods were compared: CAD/3D printing, light-cured resin, and impression compound trimming. Prosthodontist satisfaction was assessed using a visual analog scale, and manual fabrication time was analyzed. Dislocation tests were performed to evaluate tray retention. The CAD/3D printing method achieved the highest satisfaction across most parameters (P < 0.05), the best stability and retention (P < 0.05), and significantly reduced manual fabrication time (P < 0.05). The light-cured resin method showed moderate performance, while the impression compound trimming method scored lowest. The CAD/3D printing technique enhances satisfaction, precision, and efficiency, demonstrating significant potential for optimizing prosthodontic workflows. Further exploration in broader clinical applications is recommended.